Flows in Agro-food Networks (FAN): An agent-based model to simulate local agricultural material flows. (April 2020) - Fernandez-Mena, Hugo; Gaudou, Benoit; Pellerin, Sylvain; MacDonald, Graham K.; Nesme, Thomas
Highlights: We present an agent-based model: Flows in Agro-food Networks (FAN). FAN aims to simulate complex material exchanges at the local scale. FAN is applied to simulate material exchanges for a small region in France. The number of flows is sensitive to distance and shared interest between agents. FAN provides a proof of concept of farming circular economy. Abstract: Agro-food networks are characterized by complex material exchanges among farms, processors, consumers, and waste managers involved in fertilization, food, feed and bioenergy production. Better coordination of material exchanges at the local scale can facilitate more efficient resource use. Here, we present a new agent-based model, "Flows in Agro-food Networks" (FAN), which simulates the processing and exchange of fertilizers, feed, food and wastes among farms and multiple upstream or downstream partners (feed and fertilizer suppliers, food industries, waste processors, and anaerobic digesters) in small farming regions. FAN includes a series of environmental indicators that can be used to assess alternative scenarios in terms of ecosystem services, nutrient cycling, and resource autonomy. We use a French case study to demonstrate FAN's dynamics and to explore the sensitivity of key parameters. We show a strong influence of spatial distance between agents, their disposition to exchange, and their preference for specific materials on local agro-food network simulations. FAN is powerful theoretical tool to explore and assess opportunities for a circular economy in small farming regions and to unravel interactions between recycling, environmental performance and food production.